IMPLEMENTASI FUZZY LOGIC DALAM SISTEM PAKAR UNTUK MENDETEKSI PENYAKIT KANKER SERVIKS - Siti Rochana, Andriani KKW, Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2017)
Cervical cancer is one of the most frequent cancer in women with the incidence and death rate from cervical cancer is quite high and is expected to continue to rise. This research will be discussed how to detect cervical cancer by implementing fuzzy logic. Fuzzy logic used is fuzzy Tsukamoto. The input parameters in the form of symptoms such as bleeding, vaginal discharge, pelvic pain, weight loss, and bladder pain. Based on 10 cases tested, there were 8 cases properly, so that the system test results by 80%.Keyword : Cervical Cancer, Fuzzy Logic, Fuzzy Inference System, Tsukamoto.